2016
DOI: 10.1039/c6ra04930c
|View full text |Cite
|
Sign up to set email alerts
|

In situ generation of dihydropyridine for the enantioselective transfer hydrogenation of 1,4-benzoxazines

Abstract: A new strategy for the enantioselective transfer hydrogenation of benzoxazines involving an in situ generation of Hantzsch ester has been developed. Dihydroadducts were isolated in good yields (75–99%) and enantioselectivities (89–96% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Our computations predict that remote sterics exert little stereocontrolling effect; this correlation is consistent with the reduction of all known cyclic imines involving Hantzsch esters, in which proximal sterics dictate the level of stereoinduction. An optimal catalyst for such a reaction has large proximal sterics, some examples where this general trend is observed are given in Table . The catalyst entries 6 and 7 (Table ) present similar proximal steric environments but yet the enantioselectivities are very different.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Our computations predict that remote sterics exert little stereocontrolling effect; this correlation is consistent with the reduction of all known cyclic imines involving Hantzsch esters, in which proximal sterics dictate the level of stereoinduction. An optimal catalyst for such a reaction has large proximal sterics, some examples where this general trend is observed are given in Table . The catalyst entries 6 and 7 (Table ) present similar proximal steric environments but yet the enantioselectivities are very different.…”
Section: Resultsmentioning
confidence: 84%
“…If the imine is cyclic, the optimal catalyst is dependent on the nature of the nucleophile. For symmetrical nucleophiles like Hantszch esters only proximal sterics affect the TS to an appreciable extent and so the optimal catalyst has large proximal sterics disfavoring the Type II competing pathway . For Type I pathways with displaced nucleophiles the competing Type II TS arranges the imine towards a tilted disposition due to a greater steric accessibility, as a consequence both proximal and remote sterics play important stereochemical roles.…”
Section: Resultsmentioning
confidence: 99%
“… The products were obtained in good yields (up to 96%) and enantioselectivities (up to 90%). Based on this method, the parent 3-tosylaminoquinoline could be transformed in five steps into ( R )-sumanirole 1349 , the first selective agonist of the dopamine D 2 receptor …”
Section: Synthesis Of 1234-tetrahydroquinolines By Partial Hydrogenat...mentioning
confidence: 99%
“…Following the pioneering work of Zhou relying on the elegant combination of transition-metal-and organocatalysis, [73] Pélinski et al reported a new, purely organocatalytic strategy for the ATH of 1,4-benzoxazines relying on in situ formed dihydropyridine hydrogen sources (Scheme 26). [74] The multicomponent reaction of NH 4 HCO 3 , formaldehyde and ethyl acetoacetate led to the in situ generation of HE 3 and the substrates 71 a-g could be reduced in 91-99 % yield and in 89-96 % ee. Even though such a nonpolar reaction medium is generally not suitable for the synthesis of Hantzsch esters, its immediate consumption in the subsequent ATH reaction could readily shift the equilibrium, ensuring high reactivity.…”
Section: Asymmetric Transfer Hydrogenation Of N-heterocyclesmentioning
confidence: 99%
“…ATH of N-heterocycles via Ru/CPA catalysis.Scheme 26. ATH of 1,4-benzoxazines with in situ formed Hantzsch esters [74].…”
mentioning
confidence: 99%